KONSEP PENDIDIKAN ISLAM INTEGRALISTIK: Studi Pemikiran Buya HAMKA dan Mohammad Natsir - Agung Wahyu Utomo; Dartim Dartim (Universitas Muhammadiyah Surakarta, 2020)
This study aims to determine the thoughts of Buya Hamka and Mohammad Natsir regarding integralistic Islamic education and to identify the similarities and differences in the thoughts of the two figures regarding integralistic Islamic education. This research is motivated by the development of Islamic education in Indonesia as well as the covid-19 pandemic. Therefore, the concept of integralistic Islamic education which combines worldly and ukhrawi elements becomes one of the solutions in the midst of educational change. Buya Hamka and Mohammad Natsir are national Islamic figures who lived at the same time but have different educational backgrounds.This type of research is a type of library research (library research). The research approach in this study uses historical and philosophical approaches and data analysis uses history and comparative analysis. The results of this study conclude that the concept of integralistic Islamic education thought according to Buya Hamka and Mohammad Natsir is guidance that combines ukhrawi elements (morals, spiritual, emotional) and worldly elements (intellect, body, skills) based on tawhid to complement human nature and lead humans to their original nature. Then the similarity of the two concepts is in the meaning, educational goals, students, and material that must cover the science of religion and the world. While the differences appear in the curriculum, educators, educational environment, and learning methods.